Multipactor predictions for ion cyclotron resonance heating antennas of the tokamak WEST - Eva Al Hajj Sleiman; Julien Hillairet; Mohamed Belhaj; Sarah Dadouch; Vincent Maquet (Nuclear Fusion, 2023)
During the plasma experimental campaigns performed on the tokamak WEST, a performance-limiting observation has been made on the Ion Cyclotron Resonance Heating (ICRH) system composed of three identical antennas. When only one antenna is powered while the remaining two are off, an increase in the internal pressure is measured within the non-powered antennas. The internal pressure of the non-powered antennas exceeds a safety pressure interlock whose threshold is $4.5× 10^{-3}$ Pa, and consequently, the application of the RF power is prohibited to avoid plasma creation within these antennas. In this paper, the multipactor phenomenon caused by the inter-antennas’ coupling is shown to be responsible for the pressure increase observed in the non-powered antennas. Additionally, an analytic estimation of the pressure rise caused by the multipactor is compared to that observed experimentally.